2020
DOI: 10.1177/0145561320976411
|View full text |Cite
|
Sign up to set email alerts
|

Otological IgG4-Related Disease With Inner Ear Involvement: A Case Report and Review of Literature

Abstract: Immunoglobulin G4-related disease (IgG4-RD) is a chronic inflammatory disease involving multiple organs. Some studies have reported otological manifestations of IgG4-RD, although most studies describe involvement of the middle ear, and reports on inner ear manifestations are limited. Here, we describe a case of a 30-year-old man with IgG4-RD involving the inner ear. This case demonstrated that IgG4-RD affected the inner ear and caused cochlear ossification. Cochlear implants may be considered for milder cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…1 After an extensive literature review on otological IgG4-RD, we found 23 reported cases. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 According to these case studies, otalgia, worsening hearing loss, tinnitus, and vertigo constitutes otologic manifestations. Acute recurrent mastoiditis, 7 serous otitis media, 12 otorrhea, 10 and facial weakness 11 are the main clinical presentations.…”
Section: Discussionmentioning
confidence: 99%
“…1 After an extensive literature review on otological IgG4-RD, we found 23 reported cases. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 According to these case studies, otalgia, worsening hearing loss, tinnitus, and vertigo constitutes otologic manifestations. Acute recurrent mastoiditis, 7 serous otitis media, 12 otorrhea, 10 and facial weakness 11 are the main clinical presentations.…”
Section: Discussionmentioning
confidence: 99%
“…46. En cuanto a las manifestaciones otológicas relacionadas con ER-IgG4, la mayoría de los pacientes presentaban hipoacusia progresiva, vértigo, tinnitus y/o otalgia, y mucho menos frecuente otorrea. El síntoma más habitual fue la hipoacusia, uni o bilateral (en algunos casos de presentación simultánea y en otros diferida la afectación del oído contralateral), con más frecuencia de transmisión aislada o mixta, por la afectación frecuente de oído medio, presentación similar a una otitis serosa (Imagen 1); sin embargo, en un importante número de los casos publicados también había afectación de oído interno, llegando incluso a desarrollar una hipoacusia profunda, precisando un implante coclear en dos de ellos 28,40 .…”
Section: Discussionunclassified
“…Otras formas de presentación infrecuentes fueron parálisis facial periférica 13,20,27,31,34 habitualmente por infiltración pseudotumoral (Imagen 4), otorrea 19,28,40,43 por sobreinfección de una perforación timpánica o formación de granulomas inflamatorios, parestesias faciales (por afectación del V par), nódulos 25,44 auriculares, mastoiditis recurrente, acúfeno pulsátil o fístula retroauricular 15 .…”
Section: Discussionunclassified
“…Immunoglobulin G4-related disease has been documented in the sinuses, larynx, ears, and salivary glands, among other locations within the head and neck. [21][22][23] The disease is diagnosed partly by biopsy of the tissue, revealing infiltration of IgG4 positive plasmacytes. Additionally, serum levels of the antibody IgG4 can be used to aid the diagnosis and response to glucocorticoids.…”
Section: Immunoglobulin G4-related Diseasementioning
confidence: 99%